Pharmacokinetic and Pharmacodynamic Interactions Between Concomitantly used Gliclazide with Pravastatin (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Diabetic hyperlipidemia is associated with increased lipoproteins in the blood hence, the introduction of a lipid lowering drugs aids in controlling the same. This comedication may lead to drug–drug interactions between anti-diabetic and anti-hyperlipidemic drugs. The current research is aimed at evaluating the pharmacodynamic and pharmacokinetic interactions of gliclazide (anti-diabetic) therapy by pravastatin (anti-hyperlipidemic) when administrated in combination. The studies conducted on rats dosed with gliclazide, pravastatin individually and in combination. Statistical comparisons of plasma concentration – response study in groups with gliclazide alone, pravastatin alone and in combination was carried out. The response study among concentrations and time were calculated employing student’s paired T-Test. The results indicate that gliclazide is completely absorbed with peak plasma concentration of 6.82±0.12 ng/ml and 7.82±0.12 ng/ml when administrated alone and 7.22±0.12 ng/ml and 7.22±0.12 ng/ml when administrated in combination in diabetic rats on first day (day 1) and eighth day (day8) respectively. Similarly peak plasma concentration of pravastatin are 3.92±0.03 ng/ml and 4.80±0.04 ng/ml when administrated alone and 3.683±0.02 ng/ml and 4.657±0.04 ng/ml when administrated in combination in diabetic rats on first day (day 1) and eighth day (day 8) respectively.There was no statistically noteworthy variation observed in peak plasma concentration (P>0.05). Similarly no variations observed in values of tmax, AUC and T1/2. The fasting serum glucose concentrations in normal and STZ-induced diabetic group on first day (day 1) and eighth day (day 8) were analyzed. The reduction of blood glucose levels at different time intervals on administration of gliclazide and pravastatin alone and in combination analyzed and results indicate no significant change in pharmacodynamic parameters.Hence the results conclude that combinational therapy of gliclazide and pravastatin were found safe and highly potential in treating hyperlipidemia patients.